Studies on fatty acid-binding proteins. The binding properties of rat liver fatty acid-binding protein. - Wilkinson, T C (1987)
1. The fluorescent fatty acid probe 11-(dansylamino)undecanoic acid binds to rat liver fatty acid-binding protein with a 1:1 stoichiometry. 2. The binding of the fluorescent probe is competitive with long-chain fatty acids. 3. Binding displacement studies were performed with a wide range of fatty acids and other ligands and identified C16 and C18 fatty acids as the preferred fatty acids for rat liver fatty acid-binding protein. No preference was observed for unsaturated fatty acids within this group. 4. Fatty acyl-CoA binds less well than the corresponding fatty acid.